2014
DOI: 10.1002/oby.20704
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-year weight change, waist circumference change and incident obesity: The Australian diabetes, obesity and lifestyle study

Abstract: Objective: This study aimed to describe the changes in weight and waist circumference (WC), examine the incidence of obesity as defined by body mass index (BMI) and WC, and describe the changes in the prevalence of obesity over 12 years. Methods: In 1999/2000, 11,247 adults aged 25 years were recruited from 42 randomly selected areas across Australia. In total, 44.6% of eligible participants completed follow-up in 2011/12. Height, weight, and WC were measured at both surveys. Results: People who were 25-34 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
50
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 27 publications
15
50
0
1
Order By: Relevance
“…Furthermore, Tehran is a metropolitan city with different levels of population diversity and environmental risk factors compared with smaller towns in the country. Similar to ours, several studies have reported that the prevalence of abdominal obesity is growing using a cohort design (10,37) or multiple crosssectional surveys (32,38) . Niu et al (37) used longitudinal data from the China Health and Nutrition Survey (CHNS) from 1997 to 2009 and reported that the prevalence of abdominal obesity increased from 17·3 % to 39·4 % during a 12-year follow-up; in that study abdominal obesity (WC ≥ 90 cm for men and ≥80 cm for women) was more prevalent in Chinese women at baseline, but the increasing trends were observed in both genders and all age groups.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Furthermore, Tehran is a metropolitan city with different levels of population diversity and environmental risk factors compared with smaller towns in the country. Similar to ours, several studies have reported that the prevalence of abdominal obesity is growing using a cohort design (10,37) or multiple crosssectional surveys (32,38) . Niu et al (37) used longitudinal data from the China Health and Nutrition Survey (CHNS) from 1997 to 2009 and reported that the prevalence of abdominal obesity increased from 17·3 % to 39·4 % during a 12-year follow-up; in that study abdominal obesity (WC ≥ 90 cm for men and ≥80 cm for women) was more prevalent in Chinese women at baseline, but the increasing trends were observed in both genders and all age groups.…”
Section: Discussionsupporting
confidence: 78%
“…Niu et al (37) used longitudinal data from the China Health and Nutrition Survey (CHNS) from 1997 to 2009 and reported that the prevalence of abdominal obesity increased from 17·3 % to 39·4 % during a 12-year follow-up; in that study abdominal obesity (WC ≥ 90 cm for men and ≥80 cm for women) was more prevalent in Chinese women at baseline, but the increasing trends were observed in both genders and all age groups. On the other hand, Tanamas et al (10) showed in a 12-year longitudinal study that the mean BMI and WC increased in Australian adults and most prominently in those who were younger at baseline; the incidence of obesity and abdominal obesity also increased in both sexes, but was more prominent in women. The root causes behind these sex differences are unclear and need more investigations; but the higher trends of abdominal obesity in Tehranian men compared with women may in part be because, in recent years: women's awareness of their health and body has increased; women are getting more educated and involved in social activities; and last but not least, most of the public educational programmes have targeted women, somehow overlooking the male population.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that, by using BMI alone, large and increasing segments of the burden of preventable ill-health related to adverse adiposity go unrecognised ( Figure 1, grey shading). 12,13 According to an…”
Section: Changing Needs In Changing Landscapesmentioning
confidence: 99%
“…Improved identification at a population level of those at increased health risk would lead to better prioritisation of policy and resources. (22) 1988 -1994 to 2005 -2006 Waist circumference has increased more than BMI (on average by 0.86 cm) Scotland (20) …”
Section: Actions and Solutionsmentioning
confidence: 99%
“…An Australian study has shown that young people of 25-34 years of age experienced an average gain in weight of 6.7 kg and in waist circumference of 6.6 cm during 12 years. The corresponding figures for older people > 70 years were loss in weight of 4.5 kg and gain in waist circumference of 0.8 cm [14]. The gain in BMI and particularly waist circumference of this relatively young group of seafarers is therefore considerably higher than could be expected.…”
Section: Discussionmentioning
confidence: 80%